Electron microscopy as a reliable tool for rapid and conventional detection of enteric viral agents: a five-year experience report - Arcangeletti, M.C.; De Conto, F.; Pinardi, et al., F. (Acta Biomedica Atenei Parmensis, 2005)
Background and aim of the work: Since the introduction of the electron microscope and its subsequent development, virology has made a great step forward by the improvement of the basic knowledge on viral structure, as well as by broad application of electron microscopy (EM) to viral diagnosis. In this report, we describe a five-year experience in the use of EM for the diagnosis of enteric viral infections. Methods: Three thousand four hundred and ninety stool specimens were analyzed at the Virology Unit (Section ofMicrobiology, Department of Pathology and Laboratory Medicine, University of Parma, Italy) during a fiveyear period, from January 1999 to January 2004. The faecal extracts were subjected to EM after negative staining and were simultaneously cultured to evidence the presence of cytopathogenic agents. Results: EM directly applied to the above specimens allowed the detection of several enteric viral agents, particularly evidencing those normally hard to cultivate (thus easily lost with culture methods). It also enabled diagnosis of dual gut infections, such as those from rotavirus and calicivirus.On the other hand, EM-based identification of viral agents after cell culture and ultracentrifugation of cytopathogenic agent-containing cellular extracts, allowed the identification of cultivable agents, such as picornaviruses, which can escape the direct EM detection if low concentrated. Conclusions: A rationalized use of EM on selected samples, such as stool, appears suitable in epidemiological or clinical conditions when a very rapid diagnosis is required to save time, including cases of suspected emerging viral infections.